2017
DOI: 10.1136/annrheumdis-2017-212008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the change in structural radiographic sacroiliac joint damage after 2 years of etanercept therapy (EMBARK trial) in comparison to a contemporary control cohort (DESIR cohort) in recent onset axial spondyloarthritis

Abstract: ObjectiveTo compare 2 years of radiographic sacroiliac joint (SIJ) changes in patients with recent onset axial spondyloarthritis (axSpA) receiving etanercept in a clinical trial (EMBARK) to similar patients not receiving biologics in a cohort study (DESIR).MethodsEndpoints were changes at week 104 per the modified New York (mNY) grading system in total SIJ score (primary endpoint) and net percentage of patients with progression defined three ways. Treatment effect was analysed with and without adjustment for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
4
29
0
5
Order By: Relevance
“…Our data from the longitudinal analysis, consistent with the findings of previous studies , showed a positive and independent association between elevated CRP level, the presence of osteitis on MRI, and progression of radiographic sacroiliitis in patients with early axial SpA. The level of osteitis on MRI could be reduced in these patients after 3 years of continuous treatment with etanercept, as previously described .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data from the longitudinal analysis, consistent with the findings of previous studies , showed a positive and independent association between elevated CRP level, the presence of osteitis on MRI, and progression of radiographic sacroiliitis in patients with early axial SpA. The level of osteitis on MRI could be reduced in these patients after 3 years of continuous treatment with etanercept, as previously described .…”
Section: Discussionsupporting
confidence: 91%
“…In another analysis of the 2‐year progression rate from nonradiographic axial SpA to AS in patients treated with etanercept, the Study Comparing Etanercept Against a Placebo for Etanercept on a Background Nonsteroidal Antiinflammatory Drug in the Treatment of Early Spondyloarthritis Patients Who Do Not Have X‐ray Structural Changes (EMBARK), almost no progression was reported over 2 years . This might again be related to a lower proportion of patients with active inflammation or a lower extent of inflammation on MRI of the SI joints, a known risk factor for progression of radiographic sacroiliitis , in the EMBARK study as compared to the ESTHER population. The evidence of a deceleration of structural damage progression in the SI joint with increasing duration of anti‐TNF therapy shown here seems congruent with the retardation of the spine progression seen in AS patients treated long‐term with TNF inhibitors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 studies showed radiographic changes at the SI joint. Minhas et al reported an odds ratio of 0.06 (95% CI 0.004, 0.99) for the change in the BASRI SI joint score (measuring radiographic change in the SI joint) in the TNFi‐treated group compared to the biologics‐naive group in the PSOAS cohort .…”
Section: Resultsmentioning
confidence: 99%
“…Такая высокая частота перехода нерентгенологического аксСпА в АС описана впервые. По результатам других когортных исследований она составляет 5-6% [9,16]. С чем связано такое большое расхождение, пока не ясно.…”
Section: Discussionunclassified